Improving access to information – defining core electronic resources for research and wellbeing - Hormia-Poutanen, Kristiina (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Research and innovation are listed as the key success factors for the future development of Finnish prosperity and the Finnish economy. The Finnish libraries have developed a scenario to support this vision. University, polytechnic and research institute libraries as well as public libraries have defined the core electronic resources necessary to improve access to information in Finland. The primary aim of this work has been to provide information and justification for central funding for electronic resources to support the national goals. The secondary aim is to help with the reallocation of existing central funds to better support access to information.